Strategies for Village Tourism Management to Promote Community-Based Economic Independence - Arsyila, Aurelia Meisya; Amirullah, Muhammad Dekky; Tiberghien, Guillaume (Tourism and Hospitality Research, 2026)
Village tourism has emerged as a strategic instrument for fostering community-based economic independence, particularly in rural areas of developing countries. Indonesia has extensively adopted the Community-Based Tourism (CBT) approach to empower local communities, optimize local resources, and promote sustainable development. However, despite the growing number of tourism villages, many still face challenges related to governance, community participation, human resource capacity, and economic sustainability. This study aims to synthesize and analyze strategic village tourism management practices that promote community-based economic independence through the CBT framework. Using a qualitative systematic literature review of 40 peer-reviewed journal articles and conference proceedings published between 2016 and 2023, this study applies thematic analysis to identify dominant strategies, institutional patterns, and success factors. The findings reveal that effective village tourism management is driven by five interrelated strategies: participatory governance, local economic empowerment, institutional strengthening, innovation-based product development, and multi-stakeholder collaboration. The study also highlights the importance of local wisdom, financial transparency, and community ownership in sustaining economic benefits. This article contributes theoretically by consolidating fragmented CBT literature into an integrated strategic framework and practically by offering policy-relevant insights for village tourism managers and policymakers. The findings support the role of CBT as a viable pathway toward inclusive and sustainable rural economic independence.